KESIAPAN TENAGA KERJA BALI DALAM MENGHADAPI PERDAGANGAN BEBAS - Made Antara (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2012)
Employment is one of the economic indicators that show the situation and socio-economic conditions of a region. The high unemployment rate shows the narrowness of employment opportunities caused by not develop of regional economic. Conversely, the low unemployment showed developing of economic activity in that region, because it can create employment opportunities. Therefore, policies that lead to the creation of employment opportunities should be taken by the executive of a region. Over the last four years (2007-2010), labor force, not the labor force and population of work absolutely tend to increase parallel with the increasing of the total population of Bali and the work age population (over 15 years). Meanwhile, unemployment tends to decline. This is caused by an increase of the work age population are accommodated by the developing of the tourism service sector and the informal sector. Proportion of the Bali labor force that works sectorally shifts significantly over the last four years (2007-2010), especially the labor force who work on agriculture declined, and labor force who work on social service sector, social and individual increase. In the same period, absolutely number of population who work in the formal and the informal sector increased, but relatively people who work in the formal sector declined, which is compensated by an increasing the population working in the informal sector. There was a drastic increase of Bali labor power placement to abroad over the last three years (2008-2010). This indicates that the interest of workers in Bali, especially young workers to work abroad is huge. Tourism in Bali has become the engine creator of employment opportunities significantly. Increased tourist arrivals who accompanied increased of tourist spending, the more increased (demand) several of output produce by economy sectors, ultimately creating more employment opportunities. Labor force of Bali Provincial, particularly labor force graduate from Tourism Vocational High School, Diploma I, II, III, or IV of Tourism which dominates of the Balinese young labor force are very ready to compete in the era of free trade to meet the demand of professional manpower from abroad.